Prevalence of Parasitic Diseases among Internally Displaced Persons, Ethiopia, 2024 - Yohannes Shimelis Masresha; Gizachew Tadesse Wassie; Carolyn Strobel; Francisco Averhoff; Gavin Cloherty; Steven S. Yoon (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Parasitic diseases remain a major public health concern globally, particularly among vulnerable populations such as internally displaced persons (IDPs), i.e., people who relocate within their own countries due to conflict, natural disasters, or other crises. We assessed the prevalence and associated factors of schistosomiasis, geohelminthiasis, and anemia among IDPs in Ethiopia. We conducted a cross-sectional survey during March and April 2024 among IDPs in camps located in Debre Birhan, Ethiopia. Stool specimens were examined for Schistosoma mansoni and geohelminths, and urine samples were analyzed for Schistosoma hematobium . Hemoglobin concentrations were measured using a HemoCue hemoglobinometer on capillary blood samples. A total of 412 IDPs were enrolled in the study. Overall prevalence of at least one parasite was 25.7% (106/412), of whom 91.5% (97/106) had a single parasitic infection and 8.5% (9/106) had two or more. Schistosomiasis was detected in 2.4% (10/412) of participants and anemia was observed in 32.5% (134/412). Soil-transmitted helminthiases were associated with inadequate handwashing practices (adjusted odds ratio [AOR] = 2.7; 95% CI: 1.16–5.80) and inconsistent footwear use (AOR = 2.6; 95% CI: 1.3–5.1). The observed prevalence of soil-transmitted helminthiases and the significant burden of anemia underscore the need for screening and targeted interventions, including hygiene promotion; increased latrine accessibility; improved water, sanitation, and hygiene infrastructure; and consistent use of protective footwear among IDPs living in collective camps.